2010
DOI: 10.3109/07853891003652534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Xuezhikang on coronary events in hypertensive patients with previous myocardial infarction from the China Coronary Secondary Prevention Study (CCSPS)

Abstract: This study, for the first time, demonstrated that long-term Xuezhikang therapy resulted in significant reduction in cardiovascular events and death in Chinese hypertensive patients with previous MI in a safe manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…And until now, the efficacy of CM for treating hypertension is suggested by a large number of published case series and uncontrolled trials [26–30]. Six randomized controlled trials [3136] reported significant reductions in BP relative to randomly assigned control groups treated for 4 to 12 weeks, whereas the other six trials [3742] reported negative results of CM relative to control subjects. For seeking the best evidence of CM in making decisions for hypertensive patients, a number of clinical studies have been conducted in China to gain credibility with the researchers' unremitting efforts.…”
Section: Introductionmentioning
confidence: 99%
“…And until now, the efficacy of CM for treating hypertension is suggested by a large number of published case series and uncontrolled trials [26–30]. Six randomized controlled trials [3136] reported significant reductions in BP relative to randomly assigned control groups treated for 4 to 12 weeks, whereas the other six trials [3742] reported negative results of CM relative to control subjects. For seeking the best evidence of CM in making decisions for hypertensive patients, a number of clinical studies have been conducted in China to gain credibility with the researchers' unremitting efforts.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] The real clinical benefits of statins are due to their LDL-C lowering effects and this benefit has been observed in clinical trials. Rosuvastatin has been approved for use at doses of 5 -40 mg to reduce LDL-C and improve HDL and other parameters in dyslipidemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial of secondary prevention intervention conducted in China (Fig. 1) on a population of 4780 patients with coronary heart disease, of which 1445 over the age of 65, with follow-up of 7 years, gave surprising results in terms of reducing the risk of lethal and non-lethal recurrent events, probably compromised by the lack of other active interventions on patients considered [6].…”
Section: Monacolinmentioning
confidence: 97%